2017
DOI: 10.1038/bjc.2017.119
|View full text |Cite|
|
Sign up to set email alerts
|

The oral VEGF receptor tyrosine kinase inhibitor pazopanib in combination with the MEK inhibitor trametinib in advanced cholangiocarcinoma

Abstract: Background:Cholangiocarcinoma is an aggressive malignancy with limited therapeutic options. MEK inhibition and antiangiogenic therapies have individually shown modest activity in advanced cholangiocarcinoma, whereas dual inhibition of these pathways has not been previously evaluated. We evaluated the safety and efficacy of combination therapy with the oral VEGF receptor tyrosine kinase inhibitor pazopanib plus the MEK inhibitor trametinib in patients with advanced cholangiocarcinoma.Methods:In this open-label,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…In an open‐label, single‐arm study, combination therapy with oral vascular endothelial growth factor receptor tyrosine kinase inhibitor pazopanib and trametinib, reported modest clinical activity with signs of possible cumulative toxicity in patients with advanced cholangiocarcinoma. The study did not achieve statistically significant improvement in 4‐month PFS over the prespecified null hypothesized 4‐month PFS ( P = .063) . Although the aforementioned phase II trials present some scientific evidence, adequately powered trials are needed to identify the most suitable regimen and patient population who may benefit from such treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In an open‐label, single‐arm study, combination therapy with oral vascular endothelial growth factor receptor tyrosine kinase inhibitor pazopanib and trametinib, reported modest clinical activity with signs of possible cumulative toxicity in patients with advanced cholangiocarcinoma. The study did not achieve statistically significant improvement in 4‐month PFS over the prespecified null hypothesized 4‐month PFS ( P = .063) . Although the aforementioned phase II trials present some scientific evidence, adequately powered trials are needed to identify the most suitable regimen and patient population who may benefit from such treatment.…”
Section: Discussionsupporting
confidence: 82%
“…The study did not achieve statistically significant improvement in 4-month PFS over the prespecified null hypothesized 4-month PFS (P = .063). 27 Although the aforementioned phase II trials present some scientific evidence, adequately powered trials are needed to identify the most suitable regimen and patient population who may benefit from such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent decades, pathway-targeted therapies made a rapid progress in solid tumors [49,50]. Previous studies found that approximately 30%~40% of ICC patients exhibited actionable mutations, such as epidermal growth factor receptor (EGFR), and fibroblast growth factor receptor (FGFR) which shed light on the molecular targeted therapies on ICC [51,52].…”
Section: Assessment Of Outcomementioning
confidence: 99%
“…Additionally, a trial has been designed that combines a PD-1 antibody, a tyrosine kinase inhibitor (TKI, lenvatinib) and GEMOX for the treatment of ICCs (NCT0395197). All studies accessing the therapeutic e cacies of TKIs (including the multitarget TKIs cabozantinib 30 , vandetanib 31 , sorafenib 32 ; the panErbB family receptor TKI afatinib 33 ; the VEGF family receptor TKI cediranib 34 ; and the combination of pazopanib and trametinib 35 ) failed to show survival improvements. The use of checkpoint inhibitor and TKIs in combination may bring hope to patients with ICC.…”
Section: Discussionmentioning
confidence: 99%